Accountability in Malaysian federal statutory bodies:influence of organizational culture, integrity, ethical climate, leadership and audit committee / Amirah Muhamad Nor - Muhamad Nor, Amirah (2003)
The research examined the concept, need and requirements for accountability in Malaysian Federal Statutory Bodies (FSBs) and how the independent variables such as organizational culture, ethical climate, transformational leadership, integrity and existence of the Audit Committee affect accountability in the FSBs. This research adopts both a quantitative and qualitative approach to understand the three types of accountability such as Managerial Accountability, Fiduciary Accountability and Public Accountability. Questionnaires were posted to 118 FSBs in Malaysia. Five Face-to-face interviews were also conducted with the President of Malaysian Institute of Integrity, three senior management of Malaysian National Audit Department and Deputy Director General of Ministry of Higher Learning to gauge their perceptions relating to the research area. Four, structured interviews with four respondents from three FSBs were conducted. Out of 118 FSBs, only 68 (57.6%) FSBs responded to the survey by returning the questionnaires. The number of questionnaires returned to the researcher were 266 (45%) out of 590 questionnaires that were mailed or sent by hand. Data was analysed using Statistical Package for Social Science (SPSS Version 14). Suggestions and comments made by respondents on ways to improve accountability, integrity, organizational culture, ethical climate, leadership and audit committee were summarised. A summary of the Auditor General’s Annual Reports on FSBs from year 2002 to 2009 was carried out. Triangulation was done to ensure that all the information from the various sources were well supported. The findings showed that FSBs must address the various challenges in order to remain relevant in promoting accountability in the public sector. There is an increasing expectation that the FSBs should, through concerted action, play an effective role in promoting a culture that values honesty, responsibility and accountability in the exercise of authority. The occurrence of mismanagement, fraud and benefit of trust among staff entrusted to carry out managerial responsibilities and non-compliance in Federal Statutory Bodies is on the rise. Public resources or funds are either misused or misappropriated. It is believed that corporate governance and risk management practices, will minimize the weaknesses that are still occurring in FSBs. Lastly, recommendations were made to policymakers, FSBs and board of directors on some of the ways to improve accountability of FSBs. It was concluded that transformational leadership, integrity, organizational culture, ethical climate and presence of audit committee can affect accountability in FSBs.